Consumer behavior in shopping malls : an exploratory study amongst students from institutions of higher learning at Klang Valley - Dahari, Zainurin (2001)
This study attempts to examine the behavior of consumers in shopping malls. The consumers in this study are students from Institution of Higher Learning at Klang Valley. The students are chosen because they have a strong purchasing power and high potential target market. Specifically, the study investigates the shopping habits and orientations of the shoppers among the students. Amongst others the study examines the frequency of mall visits, the number of different malls visited over a period of time, the monthly expenditure spent in shopping malls and the average time spent during mall visit. Differences in shopping orientations across age groups of the student are also analyzed. The non-probability sampling procedure by convenience is used in this study. The five-page of questionnaires is distributed to one hundred and thirty two students from the Public and Private Institutions of Higher Learning. The data obtained from the respondents were analyzed using frequency analysis, percentage, mean score and cross tabulation. The results showed that factors like aesthetic, exploration, social, and convenience were the main reasons why students patronize shopping malls. Students considered the interior design of the mall as the most important reason for visiting shopping mall. The students also enjoyed the mall environment, explore new things, socializing with friend, and the variety of products offered. The developers of shopping malls should ensure that they could offer numerous futuristic attractions of facilities, which will provide a very conducive and pleasant environment for shoppers to socialized and explore the mall. In addition, those facilities must be able to attract all range of age group from the young towards the older, as their requirements are difference.